ANALISIS INOVASI BISNIS DALAM MENINGKATKAN DAYA SAING BERBASIS INNOVATION CANVAS - Simamora, Lydia Anabella Lestari; Pradana, Bayu Ilham (Jurnal Kewirausahaan dan Inovasi, 2023)
This research aims to analyze the business internal and external environments of Liebe Co and to identify the innovation potentials of the company. The data of this qualitative descriptive research was acquired from three methods; they are interview, observation, and documentation. The results of the Porter’s five forces analysis indicate that the threat for Liebe Co comes from newcomers and substitute products. Then, the innovation canvas suggests that there are three innovation potentials that can be implemented by Liebe Co; they are product innovation, marketing innovation, and technological innovation.